THE ENZYMATIC STATUS FEATURES IN BLOOD LYMPHOCYTES IN CHILDREN WITH DYSFUNCTIONAL DISORDERS OF BILIARY TRACT AND THEIR ASSOCIATION WITH GIARDIASIS - N. G. Muravyeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
N the study of NAD(P)-dependent dehydrogenases activity in blood lymphocytes in children with dysfunctional disorders of the biliary tract (DDBT) and. DDBT in association with giardiasis detected significant changes in the intracellular metabolism. In children with DDBT in blood lymphocytes the levels of substrate flow decreased at the terminal reactions of glycolysis and. the tricarboxylic acid cycle, which determines the inhibition, respectively, anaerobic and aerobic cellular respiration. It's been established that in blood lymphocytes of children with DDBT, associated with giardiasis, the activity of enzymes determining the state of aerobic respiration is reduced, while maintaining the normal level of intensity of the terminal reactions of anaerobic glycolysis. Regardless of the presence or absence of giardiasis in children with DDBT the activity of pentose phosphate cycle is reduced which characterizes the inhibition of the reactions of macromolecular synthesis.